Digital Marketing Training for MSMEs in Mojosarirejo Village, Kemlagi District, Mojokerto Regency - Laksono, Puji; Imanina, Sabrina Nur (Sahwahita: Community Engagement Journal, 2025)
This article provides an overview of the development of MSMEs in Mojosarirejo Village, Kemlagi District, Mojokerto Regency with digital marketing training. The training that has been carried out above shows that many people have great potential for economic empowerment in the MSME sector. However, the era of cyber society that demands digitalization in the online buying and selling process makes MSMEs not develop. This is due to the lack of adaptation of society to technological developments. This is what makes the author and team conduct digital marketing training for people who are still not adaptive to the development of information technology in the business process. Namely, people in Mojosarirejo Village still market MSME products offline or in their respective places, while the geographical location of Mojosarirejo Village which is far from the crowd makes people's income less than optimal. Based on the results of community service in Mojosarirejo Village, Kemlagi District, Mojokerto Regency with the Asset Based Community Development (ABCD) approach, the results of the service 1) Implementation of digital marketing training for MSME actors in Mojosarirejo Village, namely digital marketing strategies, from SEO to paid advertising, and digital marketing techniques, with a primary focus on the use of Google Ads. This platform allows MSME actors to target the right audience with relevant messages, thereby helping to increase sales and brand awareness. 2) providing material related to the ethics of communicating with consumers. Such as knowing the types of consumers, the importance of the seller's brand image, verbal and non-verbal communication in business, consumer service ethics, and increasing consumer trust. This is a supporter of digital marketing training which must be supported by communication ethics in carrying out online buying and selling activities.